Konfrontasi: why Singapore was in forefront of Indonesian attacks - Mushahid Ali (2016)
Indonesia’s confrontation of Malaysia in the 1960s saw a campaign of bomb attacks against civilian targets in Singapore including MacDonald House. Several Indonesians were captured, tried and hanged. What was the objective of Konfrontasi?